The Effect Of Mozart's Music Therapy On Maternal Anxiety During The First Stage Of The Active Phase - Anggita Septyani Permatasari; Sehmawati (LPPM AN NUUR, 2021)
Background: Childbirth is a physiological event which in the process causes severe pain, even some women experience excruciating pain. Emotional tension from anxiety to fear can exacerbate the perception of pain during labor. The results of the preliminary study conducted by the author at the Kebandaran Health Center in the Pemalang Regency area in July 2018, out of 5 maternity mothers, 3 of them experienced moderate anxiety and 1 experienced mild anxiety. Mozart's music therapy is a classical music distraction technique that has a soft tone. These tones stimulate alpha waves which give the effect of calm, comfort, tranquility and provide energy to cover, distract and release tension and pain. Objective: To determine the effect of Mozart's music therapy on maternal anxiety during the first stage of the active phase. Methods: The method used in writing the case study is a library study and Holistic Midwifery Care. The instruments used were development notes using Subjective, Objective, Data Analysis, and Management (SOAP) and the HRS-A questionnaire to assess the level of anxiety. Results: Mozart's music therapy intervention was given to Mrs. R G2P1A0 during Phase 1 of Active Phase with moderate anxiety (score 23) after being given an intervention, the level of anxiety became mild (score 19). Conclusion: Mozart's music therapy intervention has been shown to have an effect on reducing anxiety levels.